Paz e segurança na Ásia Central: terrorismo e contraterrorismo na agenda da Organização de Cooperação de Xangai - Pereira, Marina Cavalcante Martins (2021)
The present work addresses issues as terrorism, counterterrorism and regional security and presents the role of the Shanghai Cooperation Organization and its measures taken regionally and internationally within its context. The innovation that this dissertation brings is its critical look at the counterterrorism actions taken by the member countries of the organization that, in some points, are at odds with what is aimed at by the SCO. Terrorism and counterterrorism are not new issues on the security and defence policy agenda. In recent decades, and especially after the attacks of September 11, 2001, in the United States of America, it was possible to notice that terrorism stood out as an object of study. Terrorist groups and organizations have become one of the main threats faced by the international community. This led States and organizations around the world to invest billions of dollars in defensive measures, aiming the strength of counter-terrorism policies and ensuring greater security at their borders. The Shanghai Cooperation Organization (OCX) emerges within a complex context of pervasive threats and plays an important role in policy formulation in the areas of defence and security of its member states in the Central Asia region. The organization's approach consists of seeking to defend regional stability and security, respecting the territorial integrity of its members, through regional elaboration of common counterterrorism policies. Thus, it is possible to notice progress in generating greater security in the region, but this does not mean that this security will remain for the long term, as many combatants and terrorist organizations that were previously present in the region are now seeking refuge in other conflicts that represent their causes and they may eventually return to their homelands with more training and improved tactics and carry out attacks.